Efektivitas Direktori sebagai Produk Kemas Ulang Informasi dalam Penyebaran Informasi di Perpustakaan Universitas Negeri Padang - Laely Nur Barokah; Rafelta Wanda; Indah Nelsya Putri (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The development of information technology has encouraged university libraries to innovate in disseminating information more effectively. Institutional repositories are present as one of the information repackaging products that aim to collect, manage, and disseminate scientific works of academicians in digital form. Repositories can be viewed as valuable assets of an institution that function as a means to improve the reputation of the institution. This study was implemented through a quantitative approach with a descriptive method. This approach was chosen to provide a systematic, factual, and accurate picture of the effectiveness of the directory as an information repackaging product at the Padang State University Library. The results of the study indicate that the use of information repackaging is in the high category in terms of reasons for use, interaction, and results felt by users, although there are still challenges in the completeness and personalization of content. This study recommends the need for continuous evaluation, development of more diverse information formats, and increasing librarian competence in understanding user needs so that the repository can function optimally as a medium for disseminating information and supporting the position of the institution.